DISCRIMINATORY POTENTIAL OF BIPHASIC MEDIUM OVER COMPENDIAL AND BIORELEVANT MEDIUM FOR ASSESSMENT OF DISSOLUTION BEHAVIOR OF TABLETS CONTAINING MELOXICAM NANOPARTICLES - Anishetty, Ranjith; Singh, Sachin Kumar; Garg, Varun; Yadav, Ankit Kumar; Gulati, Monica; Kumar, Bimlesh; Pandey, Narendra kumar; Narang, Rakesh; Mittal, Amit (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Dissolution test serves as a quality control tool for assessment of drug release from dosage form as well as a research tool to optimize new formulations. The existing guidelines by FDA, EMA, ICH, USP, etc., describe specifications for the dissolution of immediate release as well as modified release oral dosage form. However, none of them have discussed about the discriminatory potential of the medium to differentiate release profile of two or more products that are pharmaceutically equivalent. It is pertinent to add here that the pharmaceutical equivalents are not always bioequivalent. Hence, a discriminatory dissolution procedure is a must requirement to differentiate the release behavior of drug from a pharmaceutically equivalent product that contains different types and amount of excipient in the formulation. This also becomes more cumbersome when it is desirable for prediction of in vivo behavior of a drug when it is converted into a novel delivery system like nanoparticles. The reason could be the presence of excipients used to formulate drug nanoparticles into solid oral dosage form, may change the drug disintegration as well as dissolution behavior, which ultimately may lead to altered bioavailability. Methods: In this study, the nanoparticles of meloxicam were prepared using wet media milling and the milled samples were dried using spray drier. The dried nanoparticles were converted into tablet dosage form by varying the type of diluent. To one batch lactose was used and another one was containing dicalcium phosphate (DCP). The assessment of release of meloxicam from these two batches was evaluated in various dissolution media. Results: The study revealed that in all the cases the nanoparticulate tablets of Batch 1 have given increased dissolution profile as compared to marketed formulation (Muvera ), Batch 2 and controlled tablets of meloxicam. This proved that the excipients also play a major role in the release behavior of drug otherwise if it was not so, the nanoparticulate tablets of Batch 1 and Batch 2 would have given the same dissolution profile in all the tried media. Batch 1 containing lactose with a higher surface area provided more and rapid wetting of the drug by the dissolution media compared to Batch 2 that contained DCP as a major diluent. Â® Conclusion: Among all the dissolution media tried to evaluate the discriminatory power and simulation with a biorelevant medium, the biphasic medium of pH 1.8, 4.8 and 6.8 has promised to simulate with biorelevant media. However, the medium of pH 6.8 has shown the best dissolution profile. Keywords: Solubility, Compendial media, Biphasic media, Dissolution, Meloxicam.